Generalizability of Results From Dyadic Data: Participation of One Versus Two Members of a Romantic Couple Is Associated With Breakup Likelihood. (February 2021) - Park, Yoobin; Impett, Emily A.; MacDonald, Geoff
With a growing body of relationship research relying on dyadic data (i.e., in which both members of a couple are participants), researchers have raised questions about whether such samples are representative of the population or unique in important ways. In this research, we used two large data sets (Study 1: n = 5, 118; Study 2: n = 5, 194) that included participants with and without a romantic partner participating to examine if co-participation status has substantive relationship implications. Results showed that co-participation status predicted breakup even after controlling for other known predictors such as satisfaction, although the effect weakened over time (Study 2). There was also tentative evidence that factors such as conflict may be differentially related to breakup among couples in which one versus both partners participated. These findings raise caution in interpreting effects found in dyadic studies and highlight the need to be mindful of potential bias in recruitment.